METHODS OF TEACHING THE SUBJECT “BIOLOGICAL CYBERNETICS” IN HIGHER EDUCATION IN THE LIGHT OF THE REQUIREMENTS OF THE BOLOGNA PROCESS (Pedagogy of Higher and Secondary Education, 2006)
Grading is a basic method of the credit-modulus system. The increasing interest of students in the ultimate result completes more conscious and active attitude toward educational activity. The article deals with the principal methodical recommendations on the construction and of delivering the course.